Dinamika Persaingan Usaha Penerbangan di Indonesia: Tantangan Hukum dan Aspek Keselamatan - Salsadillah, Nisfa; Arafah, Adhy Riadhy (Uti Possidetis: Journal of International Law, 2025)
Background: This paper explores the critical role of the aviation industry in facilitating the transportation of goods and passengers in an archipelagic country like Indonesia. As a fast, efficient, and economical alternative for inter-island and interregional transport, aviation has become indispensable. However, the growing competition among national airline companies has led to significant challenges, with some carriers suffering losses and even facing bankruptcy. Methodology: A normative legal research approach is employed to examine the legal framework governing business competition in the aviation sector, as well as aviation safety regulations. The study further analyzes Indonesia’s obligations as a member of the international community, particularly its commitments under the International Civil Aviation Organization (ICAO). Objectives: To analyze the intersection between aviation safety and competition law in Indonesia, identifying legal challenges and ensuring fair business practices among national airline operators. Findings: The research finds that unhealthy business competition among national airline companies has led to legal disputes and interventions by the Indonesian Competition Commission (KPPU). These include findings of violations under Law Number 5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition. Such practices have not only harmed competing businesses but also threatened the sustainability of the aviation industry. Originality/Novelty: This study provides a legal perspective that integrates competition law and aviation safety regulations, an area that is often treated separately in academic discourse. It also contributes to the understanding of how Indonesia's dual obligations–to maintain market fairness and ensure international aviation safety standards–can be harmonized through effective legal mechanisms.